Patient-Specific Quality Assurance For Volumetric Modulated Arc Therapy (Vmat) Using Fluence Map Analysis Generated From Log Data - Uwais, Fatima Adel Jbri (2023)
Volumetric Modulated Arc Therapy (VMAT) is an Intensity Modulated Radiotherapy (IMRT) treatment that involves the delivery of complex beam parameters including the dynamic multi-leaf collimators (MLC) from a linac. This study aims to evaluate the accuracy of a high-resolution, digital method using linac log data for VMAT treatment verification.